Analisis Kompetensi Kewirausahaan Pengusaha Warung Kopi Terhadap Kapabilitas Kinerja Usaha di Sulawesi Selatan - Romansyah Sahabuddin; Abdi Akbar Arief; Muh. Djufri (Seminar Nasional LP2M UNM, 2019)
This study aims to analyze the relationship between entrepreneurship competence with capability performance of coffee shop in South Sulawesi Province. The kind of research used is explanatory research. The total sample determined through purposive sampling method. This study using the equipment analysis structural equation modeling. The research results explained that: 1) Entrepreneurship orientation have no significant influence on the entrepreneurial commitment, 2) Work motivation influence significantly to entrepreneurial commitment, 3) Entrepreneurship orientation significant influence to business performance, 4) entrepreneurial Commitment influence significant to business performance, 5) entrepreneurship oriented and work motivation significant influence to entrepreneurial commitment and business performance.